Baseline concentration of heavy metals in agricultural soils - Rueda-Saa, Germán; Marín-Pimentel, Gilberto Eduardo; Menjivar-Flores, Juan Carlos (Revista de Ciencias Agrícolas, 2025)
The total concentrations of heavy metals in agricultural soils in the flat and piedmont zones of Valle del Cauca (Colombia) were evaluated. A simple random sampling was performed in 489 representative sampling sites. Samples were collected in the orders mollisol, inceptisol, and vertisol soils in 13 watersheds. Concentrations of Cd, Ni, Pb, Co, Cr, As, and Hg in soils do not follow a normal distribution. In some agricultural soils, concentrations of Cr, Ni, and Co exceeded typical ranges. Cr shows warning signs in the Pescador, RUT, and Tuluá watersheds. Alarm Ni concentrations were found in Guadalajara, Pescador, RUT, San Pedro, Sonso, and Tuluá. Alert Co levels were in the Jamundí and Pescador watersheds. As, Hg, Cd, and Pb showed high variability, while Cr, Ni, and Co showed moderate variability. A factorial analysis was performed using the Kaiser Meyer-Olkin index (KMO) and Bartlett’s test of sphericity. The KMO index indicated a correlation between the elements Hg, Cr, Ni, Pb, and Co. Cr, Ni, and Co have the highest contribution to the variance of component 1. In component 2, the highest variance is inversely correlated with Hg and Pb. The research provided a baseline for the levels of heavy metals in the region’s agricultural soils. The concentrations of metallic elements are reported and compared with typical ranges found in agricultural soils.